PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA FLASHCARD DI SEKOLAH DASAR - Fenny Tanalinal Khasna; Hafifah Awalia Hafiz (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2023)
This study aims to improve student learning outcomes through the application of the Jigsaw learning model assisted by Flashcard media in class III elementary school students. The type of research used is classroom action research (CAR) with 4 stages namely planning, implementation, observation and reflection. Data analysis techniques used through two stages, namely data collection techniques and data analysis techniques. The results of this study indicate that teacher activity in cycle I reached 61% and cycle II reached 90%. While the observation of student activity cycle I reached 62.5% and cycle II reached 90.6%. As for the student learning outcomes test cycle I where students who completed 68% and who did not complete 32%. While the learning outcomes of students in cycle II increased, namely students who completed 96% and those who did not complete 4%. This proves that the Jigsaw learning model assisted by Flashcard media can improve student learning outcomes in class III MIS Al Fitrah Oesapa Kupang-NTT.